2005
DOI: 10.1063/1.2008999
|View full text |Cite
|
Sign up to set email alerts
|

Stability and turbulent transport in Taylor–Couette flow from analysis of experimental data

Abstract: This paper provides a prescription for the turbulent viscosity in rotating shear flows for use e.g. in geophysical and astrophysical contexts. This prescription is the result of the detailed analysis of the experimental data obtained in several studies of the transition to turbulence and turbulent transport in Taylor-Couette flow. We first introduce a new set of control parameters, based on dynamical rather than geometrical considerations, so that the analysis applies more naturally to rotating shear flows in … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

16
247
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 146 publications
(265 citation statements)
references
References 50 publications
(82 reference statements)
16
247
1
1
Order By: Relevance
“…To further study the scaling of angular momentum transport in rotating shear flows, we compare our measurements to those of Wendt (1933), Taylor (1936) and Richard (2001), Dubrulle et al (2005). We find a universal scaling of the torque for various rotation profiles that captures the effects of the various geometries used in the experiments summarized here.…”
Section: Introductionmentioning
confidence: 91%
“…To further study the scaling of angular momentum transport in rotating shear flows, we compare our measurements to those of Wendt (1933), Taylor (1936) and Richard (2001), Dubrulle et al (2005). We find a universal scaling of the torque for various rotation profiles that captures the effects of the various geometries used in the experiments summarized here.…”
Section: Introductionmentioning
confidence: 91%
“…Similarities between astrophysical disks and fluid flows bounded by concentric differentially rotating cylinders have motivated a number of theoretical and experimental studies of hydrodynamic and magnetohydrodynamic Taylor-Couette flows (see, e.g. Goodman & Ji 2002;Dubrulle et al 2005;Hersant, Dubrulle & Huré 2005;Stefani et al 2006). One problem of considerable interest is, for instance, the controversial question of subcritical hydrodynamic turbulence in Keplerian-like Taylor-Couette flows.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were performed with a stationary outer cylinder and all concluded that stable vertical stratification stabilizes the flow and reduces the axial wavelength of the unstable modes which bifurcate through Hopf bifurcations. In astrophysics, Keplerian flows whose angular velocity is Ω(r) ∼ r −3/2 , are always stable to infinitely small perturbations in respect to the Rayleigh criterion [8]. As a consequence of this stability, several scenarios have been recently proposed to justify the existence of turbulence in accretion disk flows.…”
mentioning
confidence: 99%
“…Ingredients other than pure shear then need to be taken into account in order to trigger instabilities and transition to turbulence in these flows. One of the most popular scenarios relies on the MagnetoRotational Instability [9] but other instabilities such as the elliptical instability [10] or non linear shear instabilities [8] have also been suggested. In 2001, Molemaker et al [11] and Yavneh et al [12] predicted that cylindrical Couette flows in a stratified fluid may become unstable even if the Rayleigh criterion for stability was verified, i.e.…”
mentioning
confidence: 99%